Development of low content Ti-x%wt. Mg alloys by mechanical milling plus hot isostatic pressing (2023)
ABSTRACT: Several authors have shown promising results using Ti and Mg to develop materials that combine the benefits of these two metals, such as their low density and absence of harmful second phases, which makes them attractive for aerospace and biomedical applications as well as for hydrogen storage. However, titanium and magnesium are almost immiscible and there are great differences in processing temperatures of these two metals. Within the techniques reported in the literature for obtaining Ti-Mg alloys, powder metallurgy and high-energy ball milling are possibly the most popular. In this work, Ti and Mg powders were mixed using a high-energy ball mill and subsequently these mixes were sintered by hot isostatic pressing (HIP), under various conditions, to obtain Ti-Mg alloys with Mg %wt. close to the limit of solubility (x < 2%wt.). The results showed the influence of the sintering parameters in the microstructure of the sintered material, which allowed us to obtain a Ti-Mg alloy instead of a composite material.